2021
DOI: 10.1590/1519-6984.232578
|View full text |Cite
|
Sign up to set email alerts
|

Drying and storage of Melanoxylon brauna Schott. seeds

Abstract: The objective of this work was to evaluate the sensitivity of Melanoxylon brauna Schott. tree legume seeds to desiccation and storage. In the drying experiment, the Melanoxylon brauna seeds were submitted to two drying conditions: a forced air circulation chamber (40.18 °C ± 0.13 and 28.48% ± 3.95 RH) and a silica gel desiccator (27.19 °C ± 1.28 and 26.19% ± 0.94 RH) for different times (0, 12, 24, 36, 72, and 144 hours). A completely randomized design in a 2 (drying methods) × 5 (drying times) factorial schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In accordance with the germination data obtained herein, seedling emergence evaluations indicate that baru seeds remained viable during storage (Figure 4 D). What was also verified in seeds of Melanoxylon brauna Schott, by Freire et al (2021) who observed high percentages (85%) of germination, when it is were maintained in a refrigerator at ± 4 ºC for up to 12 months with a water content close to 5%. Once in studies by Ribeiro et al (2018) was noted that seeds of Erythrina velutina Willd., stored at 10 ºC for up to 14 months registered germination above 90%, however, showed oscillation in the rate of seed moisture after six months of storage.…”
Section: Assay 2 Seed Storagementioning
confidence: 55%
“…In accordance with the germination data obtained herein, seedling emergence evaluations indicate that baru seeds remained viable during storage (Figure 4 D). What was also verified in seeds of Melanoxylon brauna Schott, by Freire et al (2021) who observed high percentages (85%) of germination, when it is were maintained in a refrigerator at ± 4 ºC for up to 12 months with a water content close to 5%. Once in studies by Ribeiro et al (2018) was noted that seeds of Erythrina velutina Willd., stored at 10 ºC for up to 14 months registered germination above 90%, however, showed oscillation in the rate of seed moisture after six months of storage.…”
Section: Assay 2 Seed Storagementioning
confidence: 55%
“…The observed results indicate that storage for 12 months in an environment without temperature control (mean of 24 °C) enhances the process of deterioration of M. caesalpiniifolia seeds. Storage at room temperature also promoted faster loss of viability of Caesalpinia echinata seeds, at three months (Hellman et al, 2006), Tabebuia caraiba seeds, at three months (Guedes et al, 2012b), Myracrodruon urundeuva seeds, at 150 days (Guedes et al, 2012a) and Melanoxylon brauna seeds, at 24 months (Freire et al, 2021), compared to colder temperatures.…”
Section: Resultsmentioning
confidence: 99%